Effect Of Mercury On Tomato Growth And Yield Attributes - CH.CHANDRA SHEKAR; D.SAMMAIAH; T.SHASTHREE; K.JAGANMOHAN REDDY (International Journal of Pharma and Bio Sciences, 2011)
In the present investigation, the seeds of (Lycopersicon esculentum Mill.) variety Pusa Ruby were used to evaluate as to what effect this heavy metal mercury would create on the vegetable crop plant at different stages of its growth and development. The heavy metal mercury does and duration of treatment at optimal and suitable level was finalized after trial experiments conducted by considering present germination and seedling growth. At lower concentration treatment showed enhanced percentage of germination, survival percentage, plant height, root length, early flowering more pollen viability, increase in total chlorophyll content. Apart from this metal analysis was also studied. Different yield components such as number of fruits / plant, fruit weight and fruit girth were under taken. The higher concentration of heavy metal mercury treatments showed inhibitory effect in general. The results were discussed in relation to treatment and concentration of heavy metal mercury.